River, Culture and Tourism in Lok Baintan, South Kalimantan - Ellyn Normelani (Journal of Indonesian Tourism and Development Studies, 2016)
River become integral part of the Banjarese live in Lok Baitan, South Kalimantan. The economic value of the river has been reported very high. Rivesr is a habitat for numerous fishes which area important for local people along rivers. Rives also provide corridor for people movement. Rivers also place for economic activity. Floating market is a market located at rivers with traditional trader and seller equipped by traditional boat called Jukung. Along the Barito River, floating market point found in two place, Muara Quin and Lok Baitan. Fruit and vegetables are become the mains items in traditional floating market in Lok Baitan. Floating market has its special value for tourism attractions. Continued decrease of youngest generation to the river-based culture economic activity has been the central aspect of the future of floating market. This situation is different for modern market, which is interested among young generation in south Kalimantan. This issue is still present and will remain of great important in the future of floating market.Keywords: culture preservation, floating market, river conservation, South Kalimantan.Â